Pengaruh Masa Kerja, Disiplin Kerja dan Motivasi Kerja terhadap Kepuasan Kerja serta Implikasinya pada Kinerja Pegawai : Studi Survey di Klinik Pratama Garcia Medika di Kabupaten Bandung Barat - Novi Elvrina; Sri Rochani Mulyani; Farida Yuliaty; Vip Paramarta; Kosasih Kosasih (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study addresses the issue of varying levels of employee performance and job satisfaction in healthcare service settings, particularly in small-scale clinics. The main objective of this research is to examine the effect of tenure, work discipline, and work motivation on job satisfaction and their implications for employee performance at Klinik Pratama Garcia Medika, West Bandung Regency. A quantitative approach was applied using descriptive and verificative methods. Data were collected through questionnaires distributed to clinic employees and analyzed using path analysis to identify both direct and indirect relationships among variables. The results show that tenure, work discipline, and work motivation each have a positive and significant effect on job satisfaction. Simultaneously, these variables also significantly influence job satisfaction. Furthermore, job satisfaction has a strong positive effect on employee performance. The analysis also indicates that job satisfaction partially mediates the relationship between tenure, discipline, and motivation with employee performance, where indirect effects are greater than direct effects in several relationships. These findings highlight the importance of improving internal factors such as discipline and motivation, alongside managing employee experience, in order to enhance job satisfaction and ultimately improve performance.